Distribution of MEFV gene mutations and R202Q polymorphism in the Serbian population and their influence on oxidative stress and clinical manifestations of inflammation. Issue 1 (December 2016) - Milenković, Jelena; Vojinović, Jelena; Debeljak, Maruša; Toplak, Nataša; Lazarević, Dragana; Avčin, Tadej; Jevtović-Stoimenov, Tatjana; Pavlović, Dušica; Bojanić, Vladmila; Milojković, Maja; Kocić, Gordana; Veljković, Andrej
Abstract Background The Mediterranean fever (MEFV ) gene codes for protein pyrin, one of the regulators of inflammasome activity in innate immune cells. Mutations in this gene are considered the primary cause of Familial Mediterranean fever, but are also found in other monogenic and multifactorial autoinflammatory diseases. The aim of the study was to determine if healthy carriers ofMEFV gene mutations and R202Q polymorphism have clinical manifestations of inflammation and impaired oxidative stress parameters. Methods One hundred DNA samples from healthy volunteers (13.3 ± 8.87 years of age (mean ± SD); range 2–35) were sequenced by ABI PRISM 310 automated sequencer (PE Applied Biosystems, Norwalk, USA). The Eurofever questionnaire was used to collect retrospectively medical history data. Oxidative stress was determined by measuring spectrophotometrically thiobarbituric acid reactive substances (TBARS) in plasma and erythrocytes, as well as advanced oxidation protein products in plasma. Superoxide dismutase (SOD) activity was determined by McCord and Fridovich method in plasma and erythrocytes, while the catalase erythrocyte activity was assessed using a catalase ELISA kit. Results We found heterozygous carriers of K695R/N mutations in 5 %, E148Q/N mutations in 6 %, R202Q homozygous polymorphism in 10 % and heterozygous R202Q alterations in 45 % of healthy volunteers. TheMEFV mutation carriers and R202Q polymorphism homozygotes reported significantly more often recurrent febrile episodes (p = 0.009), diffuse abdominal pain (p = 0.025), and malaise (p = 0.012) compared to non-carriers. Erythrocyte TBARS levels and plasma SOD activity were higher in persons withMEFV mutations and R202Q/R202Q (p = 0.03 andp = 0.049, respectively). Conclusions Healthy individuals may bear E148Q and K695RMEFV gene mutations, as well as R202Q polymorphism in homozygous state. The determined gene alterations contribute to a subtle oxidative stress and may be associated with more frequent episodes of fever and unspecific inflammatory manifestations. An incomplete penetrance or variable expressivity of R202Q in populations of different ethnicity could influence the expression of autoinflammatory diseases phenotype.